How can we manage Bezold abscess emergency in COVID-19 pandemic? Blind ceftriaxone and metronidazole treatment to avoid infection spread†. Issue 10 (26th October 2021) - Scarpa, Alfonso; Di Stadio, Arianna; De Luca, Pietro; Calvanese, Matteo; Viola, Pasquale; Tassone, Domenico; de Campora, Luca; Simone, Matteo; Ricci, Giampietro; Messineo, Daniela; Ralli, Massimo; Cassandro, Claudia
Abstract: Bezold abscess (BA) can be a rare complication of different forms of otitis media. We describe a rare case of BA determined by Escherichia Coli . Because of COVID-19 restriction, the surgery had to be delayed up to the swab results. To avoid infection spread, the patient was treated by blind antibiotic treatment until the surgical drainage of mastoid and neck. Thanks to the treatment with broad-spectrum antibiotics, the progression and the spread of the infection during COVID-19 investigation was avoided. Delayed surgery could expose the patient to the risk of severe brain infection caused by the E. Coli .